Introduction to the Special Section on Business and Climate Change - Chandy, Rajesh; Dowell, Glen; Mayer, Colin; Plambeck, Erica; Serafeim, George; Toffel, Michael W.; Toktay, L. Beril; Weber, Elke (Management Science, 2023)
We are pleased to present this special section of Management Science on 'Business and Climate Change'. We launched the call for papers in 2019 to draw more scholarly attention to the major risks and opportunities that climate change poses for a wide array of companies and industries and for society at large. In the four years since then, we have seen a growing number of examples o the physical manifestations of climate change that scientists had been forecasting for decades, including intensive heat waves, wildfires, hurricanes, and flooding